Review of stem cell deregulation and breast cancer: An emerging hypothesis - Kumar D.; Kutty M. (2024)
Cancer is fundamentally a cellular genetic disease capable of transferring the "disease" to the next generation of mutated cells. Similar proliferative and information transferring capacity exists in the stem cells of various organ systems in the human body. Understanding the bio-mechanism of stem cell metabolism and its regulation by signaling molecules and extracellular micro-environment is an important step toward successful prevention and treatment of cancer. According to the cancer stem cell hypothesis, both hereditary and sporadic cancers can arise from deregulation of these cancer stem cells (CSCs), triggered by genetic and environmental factors. It is shown that deregulation of normal self-renewal pathways in undifferentiated breast stem cells or progenitor cells had altered mammary system or progenitor cells, resulting in abnormally differentiated cells in human and rodent breast cancer cell lines. Breakthroughs in molecular pathways have important therapeutic implications. Hence, significant stress is laid on targeting signaling molecules and their micromilieu in breast cancer therapy.